The immunobiology of myelodysplastic neoplasms: a mini-review - Kannan, Shruthi; Vedia, Rolando A.; Molldrem, Jeffrey J. (Frontiers in Immunology, 2024)
This mini review summarizes the immunobiology of myelodysplastic syndromes, specifically focusing on the interactions between immune cells, cytokines, and dysplastic cells within the tumor microenvironment in the bone marrow. We elucidate in detail how immune dysregulation and evasion influence the initiation and progression of myelodysplastic syndromes, as well as resistance to therapy and progression to AML. In addition, we highlight a range of therapeutic strategies, including the most recent breakthroughs and experimental therapies for treating MDS. Finally, we address the existing knowledge gaps in the understanding of the immunobiology of MDS and propose future research directions, promising advancements toward enhancing clinical outcomes and survival for patients with MDS.